2001
DOI: 10.4049/jimmunol.166.7.4293
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived Factor-1-Induced LFA-1 Activation During In Vivo Migration of T Cell Hybridoma Cells Requires Gq/11, RhoA, and Myosin, as well as Gi and Cdc42

Abstract: Dissemination of T cell hybridomas in mice, a model for in vivo migration of memory T cells and for T lymphoma metastasis, depends on the chemokine stromal cell-derived factor-1 (SDF-1) and the integrin LFA-1 and correlates well with invasion into fibroblast cultures. In addition to the known role of the pertussis toxin-sensitive heterotrimeric GTPase Gi, we show that also the pertussis toxin-insensitive GTPase Gq/11 is required for dissemination and invasion. Furthermore, we show that the small GTPases, Cdc42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 56 publications
3
28
1
Order By: Relevance
“…23 In this regard, the production of MMP-1 from CXCL12-stimulated NK cells provide an additional function of the G i -coupled pathway-independent signaling that directly regulates NK-cell invasion into tissues on stimulation with CXCL12, mechanisms of which may regulate T cell invasion as described previously. 41 The CXCL12/CXCR4 pathway was first identified to be functionally important in the homing or immobilization of hematopoietic stem cells. 42 Previous studies showed that CXCL12 stimulates homing of hematopietic cells to the target organs (ie, liver), and this process was enhanced by the production of MMPs in liver.…”
Section: Discussionmentioning
confidence: 99%
“…23 In this regard, the production of MMP-1 from CXCL12-stimulated NK cells provide an additional function of the G i -coupled pathway-independent signaling that directly regulates NK-cell invasion into tissues on stimulation with CXCL12, mechanisms of which may regulate T cell invasion as described previously. 41 The CXCL12/CXCR4 pathway was first identified to be functionally important in the homing or immobilization of hematopoietic stem cells. 42 Previous studies showed that CXCL12 stimulates homing of hematopietic cells to the target organs (ie, liver), and this process was enhanced by the production of MMPs in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Studies addressing G␣ i and G␣ 13 involvement in modulation of ␣ 4 ␤ 7 -dependent lymphocyte adhesion using mutant forms of these G proteins will be of key importance to characterize their participation in this process. In addition, it has been recently reported that SDF-1␣ activates G q , which mediates LFA-1 activation during in vivo migration of T cell hybridoma cells (53). A possible activation of G q by SDF-1␣ in lymphocytes could represent an additional candidate mechanism contributing to the increase in ␣ 4 ␤ 7 adhesive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, all chemokine receptors have been shown to couple to G␣ i , with some chemokine receptors also demonstrating the ability to couple to other G proteins as well, such as G␣ q , G␣ 16 and G␣ 11 (56,57). Although the G i inhibitor, pertussis toxin (PTX), had no effect on basal cell migration, it did completely abrogate CCL22-mediated CEM cell chemotaxis (Fig.…”
Section: The G␣ I Protein Inhibitor Pertussis Toxin Abrogates the Cmentioning
confidence: 99%